Characteristics of HLA-E Restricted T-Cell Responses and Their Role in Infectious Diseases - Simone A. Joosten; Lucy C. Sullivan; Tom H. M. Ottenhoff (Journal of Immunology Research)
Human HLA-E can, in addition to self-antigens, also present pathogen-derived sequences, which elicit specific T-cell responses. T-cells recognize their antigen presented by HLA-E highly specifically and have unique functional and phenotypical properties. Pathogen specific HLA-E restricted CD8+ T-cells are an interesting new player in the field of immunology. Future work should address their exact roles and relative contributions in the immune response against infectious diseases.